M1 Macrophages Induce PD-L1 Expression in Hepatocellular Carcinoma Cells Through IL-1β Signaling - Zong, Zhaoyun; Zou, Jiahuan; Mao, Rudi; Ma, Chao; Li, Na; Wang, Jianing; Wang, Xiaoyan; Zhou, Huaiyu; Zhang, Lining; Shi, Yongyu (Frontiers in Immunology, 2019)
Hepatocellular carcinoma (HCC) is a prototype of inflammation-related cancer, harboring M1-like and M2-like tumor-associated macrophages. M1 macrophages are thought to be tumoricidal, but some studies report its pro-tumor role. The programmed cell death-ligand (PD-L) 1 expressed in HCC cells is a critical checkpoint molecule to mediate immune escape of HCC. The PD-L1 expression in HCC cells is inducible. In the present study, we ask whether M1 macrophages induce the expression of PD-L1 in HCC cells. First, an association between M1 macrophage infiltration and PD-L1 expression in HCC tissues was determined by bioinformatics and immunohistochemistry experiments. The enrichment score of M1 macrophages was correlated to PD-L1 expression in 90 HCC samples from GEO database. Besides, infiltration of CD68+HLA-DR+ M1-like macrophages correlated with PD-L1 expression level in HCC cells. Moreover, M1-conditioned media was prepared from M1 macrophages derived from THP-1 cell, RAW264.7 cell or murine bone marrow. These supernatants induced expression of PD-L1 in HCC cells. Furthermore, inflammatory cytokine IL-1β in the supernatants was identified to account for the inducible PD-L1 expression by siRNA assay and receptor blockade assay. Additionally, transcription factor p65 and IRF1 in the HCC cells were revealed by CHIP assay to mediate the inducible PD-L1 expression. All the results demonstrate that M1 macrophages induced expression of PD-L1 in HCC cells, supporting the pro-tumor role of M1 macrophages.